A Retrospective Comparison of Aeroallergen Sensitization Among Different Allergic Diseases in Guangzhou, China - Chao Yang; Qingxiang Zeng; Gen Lu; Haipian Li; Wenlong Liu (Mediators of Inflammation)
Conclusions: Our results demonstrate the distribution and differences of allergen types among common pediatric allergic diseases, providing a theoretical basis for preventing the development of different allergic diseases and avoiding aeroallergens.